Factors Associated with Condom Use Among Sexually Active U.S. Adults, National Survey of Family Growth, 2006-2010 and 2011-2013 - Nasrullah, Muazzam (J Sex Med, 2017)
BACKGROUND: Condomless sex can increase the risk of acquiring or transmitting HIV. AIM: This study characterized the prevalence of condom use at last sex, and identified factors associated with use of a condom at last sex among adults in the U.S. METHODS: A cross-sectional National Survey of Family Growth data from cycles 2006–2010, and 2011-2013 were analyzed for sexually active men and women aged 18-44 years who reported having sex (vaginal, anal or oral) with an opposite sex partner in the past 12 months. HIV-related sexual risk behaviors (SRB) in the past 12 months included sex with ≥ 4 opposite sex partners, exchanging sex for money or drugs, and sex with an injection drug user; an HIV-positive person; a male who previously had sex with a male [women only]; a male [men only]; or a partner who had sex with other partners. OUTCOMES: The outcome for this analysis was condom use at last anal or vaginal sex. RESULTS: Overall prevalence of condom use was 24.8%; only 33.8% of adults with at least one SRB reported the use of a condom. Only 46.4% of unmarried/single men (vs. 14.7% married/cohabitating men) and 32.3% unmarried/single women (vs. 14.1% married/cohabitating women) with SRB reported using a condom at last sex, and were less likely to use a condom at last sex compared to those who did not report SRB. We did not find a significant relationship between using a condom and SRB among married/cohabitating men and women. STRENGTHS AND LIMITATIONS: Our analysis adds to the literature on how condom use varies by marital status. We measured use of condoms at last or most recent sexual act, which may not reflect individual's behavior of condom use in the past. Nonetheless, condom use at last sex has been documented in earlier studies as a valid proxy of condom use over-time. CONCLUSION: Continued efforts are needed to promote condom use among heterosexual adults in the U.S., particularly those at high risk for HIV, namely individuals engaging in anal sexual acts and with multiple sex partners.